Developing Chinese Speaking Skills through Role Play Activities of Chinese Major Students, Faculty of Humanities and Social Sciences, Rajabhat Maha Sarakham University - หม่า, ฮวาน ฮวาน; เมฆเมืองทอง, ชมพูนุท; ถึงนาค, นิรุต (Chophayom Journal, 2019)
The research aimed to 1) develop Chinese speaking skill of freshmen Chinese program, Faculty of Humanities and Social Sciences, Rajabhat Maha Sarakham University, using role play to meet the 80/80, 2) compare the Chinese speaking skill of the sample after using role play to 70%, and 3) study the level of satisfaction of the sample after using the role play. The sample comprised 42 freshmen of Chinese Program, Faculty of Humanities and Social Sciences, Rajabhat Maha Sarakham University, from 1 class of the first semester 2019 by Cluster Random Sample. The instruments for this research were 1) five instructional plans for developing of the Chinese speaking skill using role play: self-introduction, my family, hobbies, asking for direction and shopping. Score assessed by three experts, as a whole, was at the highest level ( = 4.73). 2) a test of achievements on Chinese speaking skill using role play. IOC is 1.00 for each item. Discrimination is higher than 0.2 for each item, and difficulty was 0.2-0.8, reliability using the way of Kuder-Richardson KR20 was 0.9904, and 3) a satisfaction test containing five levels, when assessed by three experts which each item was suitable. The statistics employed were percentage and T-Test. The results were as follows: 1. The efficiency of developing Chinese speaking skill of freshmen Chinese program, Faculty of Humanities and Social Sciences, Rajabhat Maha Sarakham University, using the role play was 85.12/85.29, higher than the preset criterion 80/80. 2. The Chinese speaking skill of freshmen, after using role play was higher than 70% with statistical significance at the .01 level. 3. The freshmen’s satisfaction of learning activities using the role play, on the whole, was at higher level ( = 4.36, S.D. = 0.56). When specific aspects were studied, the content aspect was at the highest level ( = 4.55, S.D. = 0.54), and other three aspects were at higher level, from high to low: teacher ( = 4.42, S.D. = 0.56), evaluation ( = 4.23, S.D. = 0.60) and teaching activity ( = 4.23, S.D. = 0.61). Keywords : developing Chinese speaking skills, role play, Chinese freshmen